Monetary Union is the future of EAEU - V. S. Kuznetsov (Vestnik MGIMO-Universiteta)
The president of Russian Federation V. Putin's Order from the 10th of March 2015 to the Government and Central Bank of Russia to work on the plan of creating Monetary Union of EAEU by the 1st of September cannot be ignored by scientific community's attention of Russia and other Eurasian countries. Strategic goal of this document is pretty clear - to create an island of currency stability in the surrounding of Jamaica's Monetary nonsystem and existing monopolar and assimetric world's dollar order, to minimize the dependency of Eurasian countries on US dollar, to hold its world expansion, to freeze the process of financing of USA imbalances by all countries, to turn back the process of dollarization of Eurasian countries and world's dollarization and relieve the world's community from future financial crises. The world's financial and economic crisis of 2008-2010 has clearly shown that US monetary, credit and banking system has become a permanent source of future turmoil of world's scale. It creates a necessity to activate the process of monetary integration of countries on the regional level and transformation of the modern Jamaica's world's dollar standard into the world's multipolar monetary standard. In this article the author analyses he stages of setting up the Eurasian regional monetary order from the creation of multilateral settlement system using common regional currency unit to the introduction of Eurasian currency system with Eurasian currency unit, which can be transformed in the future into the Eurasian Economic and monetary union with common regional currency (euras), which can restrict the world's monopoly position of the dollar.